Accessibility Of Malay Traditional Islamic Literature Through The Development Of Virtual Union Catalogue System As Post-Pandemic Solution - Saidatul Akmar Ismail; Mohd Nasir Ismail; Hairani Wahab; Halida Yu; Hanis Diyana Kamaruddin; Aniza Jamaluddin; Mohamad Rahimi Mohamad Rosman (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia